Empowering Gamification-Based Mobile Learning Media To Improve Mathematics Learning Outcomes For Dyscalculia Students - Twiningsih, Anik; Gunarhadi, Gunarhadi; Musadad, Akhmad Arif (JETL (Journal of Education, Teaching and Learning), 2024)
This research aims to describe the empowerment of gamification-based mobile learning media to improve mathematics learning outcomes in cubes and blocks in fifth grade elementary school students with dyscalculia. The formulation of the problem in this research is how effective the media used in developing gamification-based mobile learning media is to improve mathematics learning outcomes in cube and block geometric materials for students with dyscalculia. The research method used in the research is development research. The research and development design uses the Sukmadinata research and development model which consists of three steps, preliminary study, development and testing. The results of this research show that the learning outcomes of the experimental class are better than the control class. Even though the results of the effectiveness test have proven that the learning outcomes of the experimental class are better than the control class, the researchers conducted an effect test to determine the magnitude of the influence of mobile learning media on the mathematics learning outcomes of cubes and blocks in fifth grade elementary school students with dyscalculia. The effect size value (d) reached 1.83, which according to Cohen's effect size is in the high category. Thus, the use of gamification-based mobile learning media has a high influence in improving mathematics learning outcomes for cubes and blocks in fifth grade elementary school students with dyscalculia. Researchers conducted an effect test to determine the magnitude of the influence of mobile learning media on mathematics learning outcomes in cubes and blocks in fifth grade elementary school students with dyscalculia. The effect size value (d) reached 1.83, which according to Cohen's effect size is in the high category. Thus, the use of gamification-based mobile learning media has a high influence in improving mathematics learning outcomes for cube and block geometric material in fifth grade elementary school students with dyscalculia. Researchers conducted an effect test to determine the magnitude of the influence of mobile learning media on mathematics learning outcomes in cubes and blocks in fifth grade elementary school students with dyscalculia. The effect size value (d) reached 1.83, which according to Cohen's effect size is in the high category. Thus, the use of gamification-based mobile learning media has a high influence in improving mathematics learning outcomes for cubes and blocks in fifth grade elementary school students with dyscalculia.